Historia de España siglo XX : 1939-1996 / Jesús A. Martínez (coord.) ; Julio Aróstegui ... [et al.] - Martínez Martín, Jesús A.Aróstegui, Julio (1939-2013) (Historia Serie Mayor)
Bibliografía: p. 509-515